The metabolic algorithm for P systems: Principles and applications - Manca, Vincenzo (Theoretical computer science, 2008)
Metabolic P systems, shortly MP systems, are a special class of P systems, introduced for expressing biological metabolism. An MP system evolution is given by a metabolic algorithm, a deterministic strategy, where the classical viewpoint on metabolic dynamics, in terms of ordinary differential equations, is replaced by suitable generalizations of chemical principles. The basic principles of MP systems are given and their main aspects are explained by means of examples of biological modeling. A new kind of regulation mechanism is outlined, which could be the basis for a more efficient construction of computational models from experimental data of specific metabolic processes.